Grinspan’s Syndrome: A Rare Case with Malignant Transformation - Numan Kökten; Lokman Uzun; Ayşe Serap Karadağ; Tülay Zenginkinet; M. Tayyar Kalcıoğlu (Case Reports in Otolaryngology)
Aim. Oral lichen planus (OLP) is one of the common chronic inflammatory, noninfectious, and precancerous oral mucosal diseases that affect the stratified squamous epithelium in adults. Grinspan et al. reported an association of OLP with diabetes mellitus and vascular hypertension and called that Grinspan’s syndrome in 1966. We aim to present a case of Grinspan’s syndrome with malignant transformation. Case Presentation. A 60-year-old man who presented with a ten-year history of OLP diagnosed clinically and histologically was referred to our otolaryngology department with a painless swallowing in the left buccal mucosa for 3 months. Clinical examination revealed several plaques, striated white lesions in the buccal mucosa bilaterally, and an exophytic tumor in the left buccal mucosa. Histopathological examination showed lichen planus bilaterally and oral squamous cell carcinoma in the left buccal mucosa. The tumor had been developed on the preexisting areas of lichen planus which had been histologically proven before. The tumor was removed completely, and the tissue defect on the buccal mucosa was repaired with a split-thickness skin graft. Conclusion. Patients with OLP should be followed up periodically in a long term at close intervals for early diagnosis of malignant transformation.